Schimke immuno-osseous dysplasia patient with early renal dysfunction harboring a novel homozygous mutation in the SMARCAL1 gene - SÖYLEMEZ, MEHMET ALİ; GEÇKİNLİ, BİLGEN BİLGE; GÜNEY, AHMET İLTER; ATA, PINAR; ARMAN, AHMET (My University, 2021)
Main findings of this syndrome are steroid resistant nephrotic syndrome (SRNS), immunodeficiency and spondyloepiphyseal dysplasia (SED). Biallelic mutations in SMARCAL1 gene cause SIOD. SMARCAL1 encodes a conserved ATP-dependent chromatin remodeling protein which is a member of Sucrose Non-Fermenting 2(SNF2) family. Case: One-year-old female referred to our clinic because of having growth retardation and developmental delay. Her parents were from the same small village. She was delivered prematurely due of preeclampsia. In neonatal intensive care unit cardiac and renal anomalies were detected. Eruption of deciduous teeth were delayed. Fine hair, microcephaly, prominent forehead, malar hypoplasia, depressed nasal bridge, bulbous nasal tip, long philtrum, thin upper lip, everted lower lip, microdontia, anteverted ears, short neck and trunk, hyperpigmented macules on trunk, protruding abdomen, tapering fingers, brachydactyly were detected. She was diagnosed with SRNS. Skeletal survey showed platyspondyly, scoliosis, shallow acetabular fossae. No pathology was observed in the epiphyses. After DNA isolation from the peripheral blood, clinical exome sequencing were performed via next-generation-sequencing. Novel homozygous c.2423_2427+9delCCAGGGGTAAGAGA mutation in the SMARCAL1 gene(NM_001127207) was detected. According to ACMG criterias it was pathogenic(PVS1,PM2, PP3). Her parents were heterozygous. Discussion/ Conclusion: SIOD is characterized with short stature,SED,immune deficiency,SRNS and dysmorphic findings. SIOD had classified into severe and mild types. In severe patients, infections, cerebrovascular disease and renal phenotype present at an earlier age. Our patient had a severe phenotype as she carried a truncating mutation. This study reveals a novel mutation and contributes to the genotype-phenotype correlation for SIOD.
Keywords: Schimke; SIOD; SMARCAL1; renal failure; nove